A Comparison of FES and SCS for Neuroplastic Recovery After SCI: Historical Perspectives and Future Directions - Duffell, Lynsey D.; Donaldson, Nicholas de Neufvillle (Frontiers in Neurology, 2020)
There is increasing evidence that neuroplastic changes can occur even years after spinal cord injury, leading to reduced disability and better health which should reduce the cost of healthcare. In motor-incomplete spinal cord injury, recovery of leg function may occur if repetitive training causes afferent input to the lumbar spinal cord. The afferent input may be due to activity-based therapy without electrical stimulation but we present evidence that it is faster with electrical stimulation. This may be spinal cord stimulation or peripheral nerve stimulation. Recovery is faster if the stimulation is phasic and that the patient is trying to use their legs during the training. All the published studies are small, so all conclusions are provisional, but it appears that more-disabled patient (AIS A and B) may need to continue using stimulation and for them, an implanted stimulator is likely to be convenient. Less-disabled patients (AIS C & D) may make useful recovery and improve their quality of life from a course of therapy. This might be locomotion therapy but we argue that cycling with electrical stimulation, which uses biofeedback to encourage descending drive, causes rapid recovery and might be used with little supervision at home, making it much less expensive. Such an electrical therapy followed by conventional physiotherapy might be affordable for the many people living with chronic SCI. To put this in perspective, we present some information about what treatments are funded in the UK and the US.